PENGEMBANGAN BAHAN AJAR MATEMATIKA BERINTEGRASI Al-QURAN MATERI ARITMETIKA SOSIAL - Mizi Mizi; Agung Hartoyo; Asep Nursangaji (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract The aim of this research is to develop mathematics teaching materials on arithmetic. The development of this research used a model named ADDIE which is limited on three steps, Analysis, Design, and Development. The quality of teaching materials was rated in terms of three criteria which are validity that using two validity questionnaires, effectiveness that using a post test and practicality that using two practicality questionnaires. The validity of teaching materials was carried out by a content and media expert. The effectiveness of teaching materials was carried out by 34 students by taking the post test in limited tryout and the practicality of teaching materials was carried out by a teacher and 34 students. This research showed that the average of validity questionnaire scores was 4.25 (very valid). Students who achieved Minimum Completeness Criteria on post test were 2.9% (very not effective). The average of practicality questionnaire scores were 4.22 (very practical) for teachers and 2.73 (pretty practical) for students. The conclusion of this research that integrated Quranic mathematics teaching materials on arithmetic are very valid, very not effective, very practical for a teacher and pretty practical for students. Keywords: Arithmetic, Integrated Quranic, Mathematics Teaching Materials